Web-based power flow analysis tool for automated distribution network control - Ortjohann E. (2017)
© 2016 IEEE. A new approaches of energy supply system management has been widely discussed due to a penetration of distributed generation based on renewable energy resources in distribution network. One approach to accomplish distribution network management is to turn a passive distribution network to be an active network like conventional transmission network, in which there is a supervisory control for grid management. However establishing the supervisory control in distribution network, the grid structure and the fluctuation of power generation from renewable energy resources have to be taken into account. Therefore, a web-based power flow analysis tool is introduced in this paper. The power flow analysis method is performed by decoupling analysis via hybrid calculation technique. Using this calculation technique brings an interconnected grids operation into distribution network, whose operation is then able to conform to transmission network. In addition, the web- and database application is provided for supporting dynamic power generation as well as forecasting process. As a consequence, the proposed tool can perform power flow analysis related to real time power generation and load, which are sequentially updated to database server. Pointing out an application of the proposed web-based power flow analysis, a grid management in combination with hierarchical control functions are demonstrated through smart grid simulator. Hence, grid management can be expressed in an automated way.